PHYTOCHEMICAL AND PHARMACOLOGICAL STANDARDISATION OF POLYHERBAL TABLETS FOR HEPATOPROTECTIVE ACTIVITY AGAINST CARBON TETRACHLORIDE INDUCED HEPATOTOXICITY (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
Literature survey revealed that phyllanthin and hypophyllanthin from Phyllanthus niruri, wedenolactone from Eclipta alba, and kutkin from Picrorhiza kurroa are responsible for hepatoprotective activity, and phenolic and flavonoids are responsible for antioxidant activity. A selected polyherbal formulation composed of 7 herbal extract mixtures such as Phyllanthus niruri, Eclipta alba, Cichorium intybus, Boerhaavia diffusa, Embelia ribes, Berberis aristata and Picrorhiza kurroa. The phytochemical evaluation was carried out by estimation of total phenolic content and total flavonoids. The antioxidant activity was compared with ascorbic acid (ASC) and Rutin as standard. The hepatoprotective activity in carbon tetrachloride induced hepatotoxicity were studied. Assessment of liver function was made by estimating the activities of SGOT, SGPT, ALP, Cholesterol, Bilirubin and Total protein. From the study it is seen that formulation exhibit significant activity.